PHYSICAL MODELING OF HORIZONTAL COMPRESSION OF THE LITHOSPHERE - Shemenda A.I. (My University, 1989)
Several geodynamic situations involve strong horizontal compression of the lithosphere that produces a high degree of its deformation or failure. This is especially true of active continental margins, collision zones, and oceanic transform faults in which there is a compressive force component. The present paper describes the physical modeling of such situations. It assumes a two-layer 'two-dimensional' model of the upper mantle in which the upper layer, representing the lithosphere, is elastoplastic, while the lower layer is a low-viscosity liquid. Under the geodynamic conditions that we have mentioned above, the lithosphere is nonuniform, and in particular does not have a uniform thickness. Therefore, in the experiments a plate with two zones of different thicknesses was used. Compression was applied to the end faces of this plate by a piston moving at a constant velocity.